Emissão de gases de efeito estufa e estoque de carbono no sistema solo-planta em função do sistema de produção e da aplicação superficial de corretivo da acidez - Alves, Michely da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Crop rotation in no tillage can increase the stock of C in the soil and reduce emissions of greenhouse gases, though the use of soil amendments can undermine these benefits. Within this approach the work aimed to evaluate the annual emission of greenhouse gases and carbon storage in the soil-plant system due to the use of different corrective of soil acidity and crop rotations in long-tillage system duration. The survey was conducted in the Experimental Farm Lageado, belonging to the Faculty of Agricultural Sciences - UNESP, located in Botucatu (SP), and was conducted in the agricultural year 2014/2015. The plots consisted of four production systems (I. System "Safra intercropped with forage"; II System "Safra - offseason."; III System "Safra - Green manure / cover plant."; IV System "Safra Fallow." ) and the subplots by two sources of acidity corrective applied in October 2012 and a control (I - Correction with dolomitic lime II - Correction with calcium and magnesium silicate III - No correction). The gas samples for the determination of CO2 flows, N2O and CH4 from soil were performed after summer season 2014/2015 and further in the winter in 2015. The quantities of straw produced in each culture medium and supply of C and N added to the soil in winter and summer crops were analyzed. They also evaluated the stocks of C and N soil at 0-10, 10-20, 20-40 cm, and C and N microbial biomass at a depth of 0-10 cm. The results were submitted to analysis of variance (p <0.05) and the means were compared using the t test (p <0.05). Crop rotations System direct sowing and the use of lime did not increase the total organic carbon stocks and total N in the soil, as little of Microbial Biomass. Although not contributed to the stocks in the soil, crop rotation with systems involving forage and green manure resulted in lower CO2 emissions especially in the harvest. On the other hand, in the autumnwinter, the residue inputs on the ground did not reduce emissions, especially N2O. The soil remediation did not increase the accumulation of CO2, however, in the comparison between the correctives, the most CO2 emission occurred with the use of silicate. The production systems with use of fodder and green manure in winter, and the use of limestone, mainly silicate, increased productivity of corn grain per unit mass of carbon equivalent emitted into the atmosphere.

A rotação de culturas em sistema de semeadura direta podem aumentar o estoque de C no solo e reduzir as emissões de gases de efeito estufa, no entanto o emprego de corretivos de solo pode prejudicar esses benefícios. Dentro deste enfoque o trabalho teve como objetivo avaliar a emissão anual de gases de efeito estufa e o estoque de C no sistema solo-planta em função do uso de diferentes corretivos da acidez do solo e de rotações de culturas em sistema de semeadura direta de longa duração. A pesquisa foi realizada, na Fazenda Experimental Lageado, pertencente à Faculdade de Ciências Agronômicas – UNESP, localizada no município de Botucatu (SP), e foi conduzida nos anos agrícolas de 2014/2015. O delineamento estatístico experimental foi em blocos casualizados dispostos em esquema de parcelas subdivididas. As parcelas foram constituídas por quatro sistemas de produção (I. Sistema “Safra consorciada com Forrageira”; II. Sistema “Safra – safrinha”; III. Sistema “Safra – Adubo Verde/Planta de Cobertura”; IV. Sistema “Safra Pousio”) e as subparcelas por duas fontes de corretivos de acidez aplicados em outubro de 2012 e uma testemunha (I – Correção com calcário dolomítico; II – Correção com silicato de cálcio e magnésio; III – Sem correção). As amostragens de gases para a determinação dos fluxos do CO2, N2O e CH4 provenientes do solo foram realizadas após a safra de verão em 2014/2015 e após a de inverno em 2015, em um total de 17 coletas de gases. Foram analisadas as quantidades de palha produzida em cada cultivo e os aportes médios de C e N adicionados ao solo no cultivo de inverno e verão. Foram avaliados também os estoques de C e N do solo nas profundidades de 0-10, 10-20, 20-40 cm, e C e N da biomassa microbiana na profundidade de 0-10 cm. Os resultados foram submetidos à análise de variância (p<0.05) e as médias foram comparadas pelo teste t (p<0.05). As rotações de culturas em Sistema Semeadura Direta e o uso de corretivos não aumentaram os estoques de C orgânico total e de N total no solo, tão pouco da Biomassa Microbiana. Apesar de não contribuir para os estoques no solo, a rotação de culturas com sistemas envolvendo forrageira e adubo verde resultaram em menores emissões de CO2 especialmente na safra. Por outro lado, no cultivo de outono-inverno, o aporte de resíduos sobre o solo não reduziu as emissões, especialmente de N2O. A correção do solo não aumentou as emissões acumuladas de CO2, porém, na comparação entre os corretivos, a maior emissão de CO2 ocorreu com o uso de silicato. Os sistemas de produção com uso de forrageira e adubo verde no inverno, e o uso de corretivos da acidez, principalmente o silicato, aumentou a produtividade de grãos de milho por unidade de massa de carbono equivalente emitido para a atmosfera.
Greenhouse gas emissions and carbon stock in the soil-plant system influenced by the production system and the surface lime application
Keywords: Crop rotation; Tillage; Greenhouse effect; Roração de culturas; Semeadura direta; Efeito estufa